Surface graft polymerization of conducting polyaniline on waterborne poyurethane‐urea film and its phenol sensing. Issue 3 (8th May 2012) - Son, Su‐Jin; Kim, Han‐Seong; Lee, Dong‐Jin; Lee, Young‐Hee; Kim, Han‐Do
Abstract: Waterborne polyurethane‐ureas (pristine WBPUs: WBPU‐19 and WBPU‐24, fixed soft segment content: 60 wt %) containing dimethylol propionic acid (DMPA)/ethylene diamine (EDA) contents (19/16.8 and 24/11.4 mol %) were prepared. The polyaniline (PANI)‐ graft ‐WBPU (PANI‐ graft ‐WBPU) films were prepared by oxidative graft polymerization of aniline on the surface layer of WBPU films. This study focused on the effects of reaction conditions (concentrations/treating times/temperatures of aniline and APS) and DMPA content on the %grafting, conductivity, and mechanical properties of PANI‐ graft ‐WBPU films. To obtain the maximum %grafting (PANI‐ graft ‐WBPU‐19: 6.2, and PANI‐ graft ‐WBPU‐24: 7.4) and conductivity (PANI‐ graft ‐WBPU‐19: 3.6 × 10 −2 S/cm, and PANI‐ graft ‐WBPU‐24: 4.7 × 10 −2 S/cm), the optimum concentrations/treating times/temperatures of aniline and APS, were found to be 0.35 M /10 min/25°C and 0.2 M /10 min/0°C, respectively. The tensile strength of film samples was found to be increased in the order of PANI‐ graft ‐WBPU‐19>pristine WBPU‐19>PANI‐ graft ‐WBPU‐24>pristine WBPU‐24. The PANI‐ graft ‐WBPU‐19 (%grafting: 6.2) films on exposure to 0–10, 000 ppm phenol solutions showed a well‐defined response behavior, demonstrating high promise for application in aqueous phenol sensors. © 2012 Wiley Periodicals, Inc. J. Appl. Polym. Sci., 2013 Abstract :